Fluoropolymer Binder
Patent Information
- Application Number
- JP2023567978
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-05-03
- Filing Date
- 2022-05-02
- Publication Date
- 2025-03-12
AI Technical Summary
Existing electrode binders for Li-ion batteries, such as polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE), face issues with adhesion, agglomeration, and environmental hazards, limiting the production of thicker electrodes with high energy density and increasing the need for solvent-based processes.
A composite binder formed from a homogeneous mixture of PTFE and PVDF particles, manufactured through co-spraying or polymerization methods, reduces binder content while ensuring adhesion and mechanical integrity, suitable for solvent-free electrode fabrication.
The composite binder enhances electrode cohesion, mechanical strength, and uniformity, allowing for thicker electrodes with increased active filler content and improved handling, flexibility, and reduced environmental impact.
Abstract
Description
[Technical field]
[0001] The present invention generally relates to the field of electrical energy storage in Li-ion type secondary batteries. More specifically, the present invention relates to a binder in the form of a powder based on a homogeneous mixture of fluoropolymers. The present invention also relates to several methods for producing said binder. Finally, the present invention relates to an electrode comprising said binder, and to an energy storage device comprising at least one such electrode, such as a Li-ion secondary battery and a supercapacitor. [Background technology]
[0002] A Li-ion battery comprises at least one negative electrode or anode bonded to a copper current collector, a positive electrode or cathode bonded to an aluminum current collector, a separator, and an electrolyte. The electrolyte is a lithium salt, typically lithium hexafluorophosphate, mixed with a solvent that is a mixture of organic carbonates. It is selected to optimize ion transport and dissociation. A higher dielectric constant promotes ion dissociation and increases the number of ions available in a given volume, while a lower viscosity favors ion diffusion. This, among other parameters, plays an important role in the charge and discharge rates of an electrochemical system.
[0003] For its part, an electrode generally comprises at least one current collector, on which is deposited in the form of a film a composite material consisting of: a material called active because it exhibits electrochemical activity towards lithium, a polymer acting as a binder, and one or more conductive additives, generally carbon black or acetylene black, and optionally a surfactant.
[0004] Binders are counted among the so-called inactive components, since they do not directly contribute to the capacity of the cell. However, their important role in the processing of the electrode and their considerable influence on the electrochemical performance of the electrode are widely known. The main important physical and chemical properties of binders are thermal stability, chemical and electrochemical stability, tensile strength (strong adhesion and cohesion) and flexibility. The main purpose of using binders is to form a stable network (cohesion) of the solid components of the electrode, i.e., active material and conductive agent. In addition, the binder must ensure an intimate contact (adhesion) between the composite electrode and the current collector.
[0005] Polyvinylidene fluoride (PVDF) is the most commonly used binder in lithium-ion batteries due to its excellent electrochemical stability, good adhesion capacity, and strong adhesion to electrode and current collector materials. However, PVDF can only be dissolved in certain organic solvents, such as N-methylpyrrolidone (NMP), which is volatile, flammable, explosive, and highly toxic, causing serious environmental problems. The use of organic solvents requires significant investment in production, recycling, and purification facilities.
[0006] Compared to the traditional method of producing electrodes in wet suspension, the dry (solvent-free) manufacturing process is simpler. Such a method offers the possibility of producing thicker electrodes (>120 μm) with reduced emissions of volatile organic compounds and increased energy density in the final energy storage device.
[0007] Polytetrafluoroethylene (PTFE) is the material of choice for dry electrode manufacturing due to its ability to fibrillate at ambient temperatures. PTFE fibrillation improves the mechanical properties of the electrode and increases its cohesion. Nevertheless, PTFE has two limitations: it does not always achieve a suitable level of adhesion to the cathode (on aluminum foil) and it needs to be combined with other binders; and PTFE undergoes reduction reactions at the anode, which significantly limits its use.
[0008] WO2015 / 161289 describes an energy storage device having a cathode, an anode, and a separator between the anode and the cathode, where at least one of the electrodes comprises a composite binder material based on polytetrafluoroethylene (PTFE). The PTFE composite binder material may comprise PTFE and at least one of the following materials: polyvinylidene fluoride (PVDF) and a copolymer of PVDF and polyethylene oxide (PEO). Example 6 describes a manufacturing method for forming a cathode electrode membrane, which includes first mixing activated carbon with powdered PVDF in a mass ratio of 2:1 for 10 minutes, followed by a step of grinding by spraying at a pressure of about 80 psi, then adding a mixed powder containing NMC, activated carbon and carbon black, and finally adding PTFE and mixing for 10 minutes.
[0009] The disadvantage of this type of composite binder is the lack of sustained cohesion, i.e. even if a homogeneous initial mixture of two or more types of particles is obtained, these particles do not adhere to each other and are therefore prone to settling phenomena during storage or transportation, thus resulting in a loss of homogeneity over time.
[0010] There remains a need to develop new electrode binders for Li-ion batteries that are suitable for dry (solvent-free) electrode fabrication.
[0011] It is therefore an object of the present invention to provide compositions and methods of manufacture for solid particle based binders and films for use in battery electrodes.
[0012] Another object of the present invention is to provide an electrode having a relatively low binder mass content to allow for an increased content of active filler in the cathode to maximize battery capacity.
[0013] The invention also aims to provide a method for the preparation of an electrode for a Li-ion battery using said composition, by a solvent-free deposition technique on a metal substrate. Finally, the invention relates to the electrode obtained by this method.
[0014] Finally, the present invention contemplates providing energy storage devices including at least one such electrode, such as Li-ion secondary batteries and supercapacitors including at least one such electrode. [Prior art documents] [Patent documents]
[0015] [Patent Document 1] International Publication No. 2015 / 161289 Summary of the Invention
[0016] The present invention relates to a binder usable in lithium-ion batteries. It is a composite binder formed from a homogeneous mixture of two fluoropolymers: PTFE and PVDF.
[0017] The present invention relates first to a fluoropolymer binder for lithium ion batteries, comprising a mixture of a PTFE phase formed from PTFE particles having a size in the range of 10 nm to 1 μm and a PVDF phase formed from PVDF particles having a size in the range of 10 nm to 1 μm, said binder being in the form of a powder.
[0018] According to one embodiment, the PVDF is selected from polyvinylidene fluoride homopolymers or copolymers of vinylidene fluoride with at least one comonomer selected from vinyl fluoride, tetrafluoroethylene, hexafluoropropylene, 3,3,3-trifluoropropene, 2,3,3,3-tetrafluoropropene, 1,3,3,3-tetrafluoropropene, hexafluoroisobutylene, perfluorobutylethylene, 1,1,3,3,3-pentafluoropropene, 1,2,3,3,3-pentafluoropropene, perfluoro(propyl vinyl ether), perfluoro(methyl vinyl ether), bromotrifluoroethylene, chlorofluoroethylene, chlorotrifluoroethylene, chlorotrifluoropropene, ethylene, and mixtures thereof.
[0019] The present invention also relates to various methods for producing said binders.
[0020] According to one embodiment, the binder is prepared by co-spraying of PVDF latex and PTFE latex, the method comprising: a. mixing PVDF latex with PTFE latex; b. adding water to the PVDF latex / PTFE latex mixture to make the dry extract have a polymer content of 10% to 50% by weight; c. Co-atomizing the mixture thus obtained to obtain a composite powder formed of particles of PTFE and particles of PVDF.
[0021] According to one embodiment, the binder is prepared by polymerizing PVDF in the presence of PTFE seeding.
[0022] According to one embodiment, the binder is prepared by polymerizing PTFE in the presence of PVDF seeding.
[0023] The present invention also provides a Li-ion battery electrode comprising an active filler, a conductive filler and a fluoropolymer binder for the anode or cathode as described above. The applicant has demonstrated that it is possible to manufacture an electrode for a lithium-ion battery containing 1% to 5% by mass of binder. This means that the amount of binder is less than in techniques where the two binders are not intimately combined, which is considered due to the need to increase the amount of binder used to achieve comparable handling, flexibility and adhesion properties. By reducing the amount of binder, the content of active filler in the cathode can be increased, and therefore the charging capacity of the latter can be increased.
[0024] The present invention also relates to a solventless process for producing Li-ion battery electrodes.
[0025] The present invention also provides a Li-ion secondary battery comprising a negative electrode, a positive electrode, and a separator, at least one of the electrodes being as described above.
[0026] The present invention makes it possible to overcome the drawbacks of the state of the art. More specifically, the present invention provides a technique that makes it possible to: -Improve the handling performance of electrode materials to reduce the binder content in the electrodes; -Controlling the distribution of binders and conductive fillers on the surface of the active fillers; -Ensuring good film formation or solidification of the formulation, thereby ensuring cohesion and mechanical integrity of the electrode, which is difficult to achieve with solvent-free processes; - Improve the uniformity of the electrode composition in the thickness and width of the electrode; - reducing the total content of binder in the electrode. In the case of known solvent-free processes, this is still more than in standard slurry processes; - improving the mechanical strength of free-standing films of the electrode formulation, which means that when the solvent-free electrode manufacturing process proceeds through the intermediate stage of manufacturing a free-standing film of the formulation before assembly on the current collector, it allows the formulation to achieve sufficient mechanical behavior for the handling and winding / unwinding steps. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] The invention is explained in more detail, in a non-limiting manner, in the following description.
[0028] According to a first aspect, the present invention relates to a fluoropolymer binder for lithium-ion batteries, consisting of a mixture of a polytetrafluoroethylene (PTFE) phase and a polyvinylidene fluoride (PVDF) phase.
[0029] The binder is characterized in that it is in the form of a powder consisting of a mixture of PTFE primary particles having a size in the range of 10 nm to 1 μm and PVDF primary particles having a size in the range of 10 nm to 1 μm.
[0030] According to various embodiments, the electrodes include the following features, in appropriate combinations: Contents listed are by weight unless otherwise stated.
[0031] According to one embodiment, the PTFE particles have a size in the range of 50 nm to 500 nm, preferably in the range of 100 nm to 300 nm.
[0032] According to one embodiment, the PVDF particles have a size in the range of 50 nm to 500 nm, preferably in the range of 100 nm to 300 nm.
[0033] Primary particles are defined herein as particles having a size less than 1 μm.
[0034] The size of the polymer particles is expressed as the volume average diameter (Dv50). Dv50 is the particle size at the 50th percentile of the cumulative particle size distribution. This parameter can be measured by laser particle size analysis.
[0035] The weight ratio of PVDF to PTFE in the binder varies from 10:90 to 90:10.
[0036] According to one embodiment, the binder is fibrillizable due to the presence of PTFE.
[0037] PVDF The fluoropolymers used in the present invention, commonly referred to by the abbreviation PVDF, are polymers based on vinylidene fluoride.
[0038] According to one embodiment, the PVDF is a polyvinylidene fluoride homopolymer or a mixture of vinylidene fluoride homopolymers.
[0039] According to one embodiment, the PVDF is a polyvinylidene fluoride homopolymer or a copolymer of vinylidene fluoride containing at least one comonomer compatible with vinylidene fluoride.
[0040] Comonomers compatible with vinylidene fluoride can be halogenated (fluorinated, chlorinated or brominated) or non-halogenated.
[0041] Examples of suitable fluorinated comonomers are vinyl fluoride, tetrafluoroethylene, hexafluoropropylene, trifluoropropene, in particular 3,3,3-trifluoropropene, tetrafluoropropene, in particular 2,3,3,3-tetrafluoropropene or 1,3,3,3-tetrafluoropropene, hexafluoroisobutylene, perfluorobutylethylene, pentafluoropropene, in particular 1,1,3,3,3-pentafluoropropene or 1,2,3,3,3-pentafluoropropene, perfluorinated alkyl vinyl ethers, in particular those of the general formula Rf-O-CF=CF2, where Rf is an alkyl group, preferably a C1-C4 alkyl group (preferred examples are perfluoro(propyl vinyl ether) and perfluoro(methyl vinyl ether)).
[0042] The fluorinated comonomer may contain a chlorine atom or a bromine atom. It may be selected in particular from bromotrifluoroethylene, chlorofluoroethylene, chlorotrifluoroethylene and chlorotrifluoropropene. Chlorofluoroethylene may mean either 1-chloro-1-fluoroethylene or 1-chloro-2-fluoroethylene. The 1-chloro-1-fluoroethylene isomer is preferred. The chlorotrifluoropropene is preferably 1-chloro-3,3,3-trifluoropropene or 2-chloro-3,3,3-trifluoropropene.
[0043] The VDF copolymer may also contain non-halogenated monomers such as ethylene and / or acrylic or methacrylic comonomers.
[0044] The fluoropolymer preferably contains at least 50 mol % vinylidene fluoride.
[0045] According to one embodiment, the PVDF is a copolymer of vinylidene fluoride (VDF) and hexafluoropropylene (HFP) (P(VDF-HFP)) having a weight percentage of hexafluoropropylene monomer units of 2% to 23%, preferably 4% to 15%, based on the weight of the copolymer.
[0046] According to one embodiment, the PVDF is a mixture of polyvinylidene fluoride homopolymer and VDF-HFP copolymer.
[0047] According to one embodiment, the PVDF is a copolymer of vinylidene fluoride and tetrafluoroethylene (TFE).
[0048] According to one embodiment, the PVDF is a copolymer of vinylidene fluoride and chlorotrifluoroethylene (CTFE).
[0049] According to one embodiment, the PVDF is a VDF-TFE-HFP terpolymer. According to one embodiment, the PVDF is a VDF-TrFE-TFE terpolymer (TrFE is trifluoroethylene). In these terpolymers, the mass content of VDF is at least 10% and the comonomers are present in various proportions.
[0050] According to one embodiment, the PVDF is a copolymer of two or more VDF-HFP copolymers.
[0051] According to one embodiment, the PVDF comprises monomer units having at least one of the following functional groups: carboxylic acid, carboxylic anhydride, carboxylic ester, epoxy group (such as glycidyl), amide, hydroxyl, carbonyl, mercapto, sulfide, oxazoline, phenol, ester, ether, siloxane, sulfonic acid, sulfur, phosphorus or phosphonic acid. The functional groups are introduced by chemical reaction, which may be grafting or copolymerization of a fluorinated monomer with a monomer having at least one of said functional groups and a vinyl function capable of copolymerizing with the fluorinated monomer, according to techniques well known to those skilled in the art.
[0052] According to one embodiment, the functional groups have carboxylic acid functional groups, which are (meth)acrylic acid type groups selected from acrylic acid, methacrylic acid, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate and hydroxyethylhexyl (meth)acrylate.
[0053] According to one embodiment, the unit having a carboxylic acid functionality further comprises a heteroatom selected from oxygen, sulfur, nitrogen and phosphorus.
[0054] According to one embodiment, the functional group is introduced by a transfer agent used during the synthesis process. The transfer agent is a polymer with a molar mass of less than or equal to 20000 g / mol and with functional groups selected from carboxylic acid, carboxylic anhydride, carboxylic ester, epoxy group (such as glycidyl), amide, hydroxyl, carbonyl, mercapto, sulfide, oxazoline, phenol, ester, ether, siloxane, sulfonic acid, sulfur, phosphorus or phosphonic acid. An example of this type of transfer agent is an oligomer of acrylic acid.
[0055] The content of functional groups in PVDF is 0.01 mol % or more, preferably 0.1 mol % or more, and 15 mol % or less, preferably 10 mol % or less.
[0056] The PVDF is preferably of high molecular weight. The term "high molecular weight" as used herein is understood to mean a PVDF having a melt viscosity of more than 100 Pa.s, preferably more than 500 Pa.s, more preferably more than 1000 Pa.s, advantageously more than 2000 Pa.s. The viscosity is measured according to the ASTM D3825 standard using a capillary or parallel plate rheometer at 232°C and 100 s. -1 The shear gradient is measured at 100 nm. The two methods give similar results.
[0057] The PVDF homopolymer and VDF copolymer used in the present invention can be obtained by known polymerization methods, for example emulsion polymerization.
[0058] According to one embodiment, they are prepared by an emulsion polymerization process in the absence of fluorinated surfactants.
[0059] Polymerization of PVDF generally results in a latex having a solids content of 10% to 60%, preferably 10% to 50%, by weight, and a weight average particle size of less than 1 micrometer, preferably less than 1000 nm, preferably less than 800 nm, more preferably less than 600 nm. The weight average size of the particles is generally 10 nm or more, preferably at least 50 nm, advantageously with an average size in the range of 100 to 400 nm. The polymer particles may form aggregates, called secondary particles, whose weight average size is less than 5000 μm, preferably less than 1000 μm, advantageously 1 to 80 micrometers, preferably 2 to 50 micrometers. The aggregates can be broken down into separate particles during formulation and application to a substrate.
[0060] According to some embodiments, the PVDF homopolymer and VDF copolymer consist of bio-based VDF. The term "bio-based" means "obtained from biomass". This makes it possible to improve the ecological footprint of the membrane. Bio-based VDF is according to the NF EN 16640 standard 14 It can be characterized by a content of renewable carbon, i.e. carbon of natural origin and carbon derived from biological materials or biomass, of at least 1 atomic %, as measured by the C content. The term "renewable carbon" indicates that the carbon is of natural origin and derived from biological materials (or biomass), as shown below. According to some embodiments, the biocarbon content of the VDF is greater than 5%, preferably greater than 10%, preferably greater than 25%, preferably greater than 33%, preferably greater than 50%, preferably greater than 66%, preferably greater than 75%, preferably greater than 90%, preferably greater than 95%, preferably greater than 98%, preferably greater than 99%, advantageously equal to 100%.
[0061] PTFE The fluoropolymers used in the present invention, commonly referred to by the abbreviation PTFE, are polymers based on tetrafluoroethylene (TFE).
[0062] According to one embodiment, the PTFE is a poly(tetrafluoroethylene) homopolymer or a mixture of tetrafluoroethylene homopolymers.
[0063] According to one embodiment, the PTFE is a poly(tetrafluoroethylene) homopolymer or a copolymer of tetrafluoroethylene and at least one comonomer compatible with tetrafluoroethylene, such as vinylidene fluoride or hexafluoropropylene.
[0064] According to one embodiment, the polytetrafluoroethylene used in the binder composition according to the invention is a polymer obtained by emulsion polymerization of TFE, in a mixture with PVDF, under conditions known to those skilled in the art.
[0065] According to one embodiment, TFE may be copolymerized with at least one other monomer, such as vinylidene fluoride or hexafluoropropylene.
[0066] Polymerization of PTFE generally results in a latex having a solids content of 10% to 60%, preferably 10% to 50%, by weight, and a weight average particle size of less than 1 micrometer, preferably less than 1000 nm, preferably less than 800 nm, more preferably less than 600 nm. The weight average size of the particles is generally greater than or equal to 10 nm, preferably greater than or equal to 50 nm, and advantageously the average size is within the range of 100 to 400 nm.
[0067] According to one embodiment, the PTFE used in the present invention has a high molecular weight, preferably above 100000 g / mol.
[0068] The present invention also relates to various methods for making the fluoropolymer binder.
[0069] co-spraying According to one embodiment, the binder is prepared by co-spraying the PVDF latex and the PTFE latex described above.
[0070] Spraying (or co-spraying) is known per se. For a general description of this technique, see, for example, the chapter "Drying" by PY McCormick in the "Encyclopedia of Polymer Science and Engineering", volume 5, pp. 187-203, Wiley Intersciences, 1990. During the preparation of the binder in powder form, the fluoropolymer is always in the form of particles with a size of less than 1 μm.
[0071] According to one embodiment, an aqueous dispersion is prepared by mixing, under stirring, a mixture of fluorinated polymer latexes (PVDF latex and PTFE latex as described above) so that the content of dry extract is between 10% and 50% by weight of the polymers PVDF+PTFE. This aqueous dispersion is then sprayed in the presence of an antifoaming agent, preferably of modified siloxane polyether type, to obtain a composite powder which can then be used for the preparation of electrodes.
[0072] Upon completion of the powder manufacturing process, the particle size can be adjusted and optimized by selection or screening methods.
[0073] Polymerization of PVDF in the presence of PTFE seeding (PVDF shell / PTFE core) According to one embodiment, the binder is prepared by polymerizing PVDF in the presence of PTFE seeding.
[0074] According to one embodiment, water is added to the reactor used for emulsion polymerization of TFE monomer and obtaining PTFE in latex form to obtain a dry extract ranging from 10% to 50%, to which vinylidene fluoride and a polymerization initiator are added. At the end of the polymerization reaction, a stable latex is obtained with a particle size ranging from 200 to 400 nm (Dv50). The PVDF:PTFE mass composition of this latex varies from 10:90 to 90:10. The solid content obtained is between 10 and 60%.
[0075] According to one embodiment, the PTFE latex is obtained in a first reactor and transferred, optionally after a period of storage, to a second reactor, where it then begins to polymerize the PVDF.
[0076] Polymerization of PTFE in the presence of PVDF seeding (PTFE shell / PVDF core) According to one embodiment, the binder is prepared by polymerizing PTFE in the presence of PVDF seeding.
[0077] According to one embodiment, water is added to the reactor used for emulsion polymerization of VDF monomers and obtaining PVDF in latex form to obtain a dry extract ranging from 10% to 50%, to which tetrafluoroethylene and a polymerization initiator are added. At the end of the polymerization reaction, a stable latex is obtained with a particle size ranging from 200 to 400 nm (Dv50). The PVDF:PTFE mass composition of this latex varies from 10:90 to 90:10. The solid content obtained is between 10 and 60%.
[0078] According to one embodiment, the PVDF latex is obtained in a first reactor and transferred, optionally after a period of storage, to a second reactor, where it then begins to polymerize the PTFE.
[0079] The present invention also provides a Li-ion battery electrode comprising an active filler, a conductive filler and a fluoropolymer binder for an anode or cathode as described above.
[0080] In the electrode material, the PTFE is fibrillated. The degree of fibrillation and the quality of the fibrils formed affect certain properties of the electrode, such as its flexibility and maneuverability. The fibrils can be seen by scanning electron microscopy (SEM).
[0081] The active materials in the negative electrode are generally lithium metal, graphite, graphene, silicon / carbon composites, silicon, CF4 where x is between 0 and 1. x Fluoro-graphite of type LiTiO 12 It is a type titanate.
[0082] The active material in the positive electrode is generally of the LiMO2 type, LiMPO4 type, Li2MPO3F type, Li2MSiO4 type, where M is Co, Ni, Mn, Fe, or a combination thereof, LiMn2O4 type, S8 type, or lithium polysulfide type represented by the formula Li2Sn, where n>1.
[0083] The conductive fillers are selected from carbon black, graphite, natural or synthetic carbon fibers, carbon nanotubes, metal fibers and powders, and conductive metal oxides. They are preferably selected from carbon black, graphite, natural or synthetic carbon fibers and carbon nanotubes.
[0084] Mixtures of these conductive fillers can also be produced. In particular, the use of carbon nanotubes in combination with another conductive filler, such as carbon black, can have the advantage of reducing the conductive filler content in the electrode and reducing the polymer binder content due to its lower specific surface area compared to carbon black.
[0085] According to one embodiment, a polymeric dispersant different from the binder is used in the mixture with the conductive filler to break up any agglomerates present and aid in their dispersion in the final formulation containing the polymeric binder and the active filler. The polymeric dispersant is selected from poly(vinylpyrrolidone), poly(phenylacetylene), poly(meta-phenylenevinylidene), polypyrrole, poly(para-phenylenebenzobisoxazole), poly(vinyl alcohol) and mixtures thereof.
[0086] The mass composition of the electrode is - 50% to 99%, preferably 50% to 99%, of active fillers, - 25% to 0.05%, preferably 25% to 0.5%, of a conductive filler, - 10% to 0.5%, preferably 6% to 1%, of a polymer binder, - 0% to 5% of at least one additive selected from plasticizers, ionic liquids, dispersants for conductive fillers, and flow agents for the formulation and the sum of all these percentages is 100%.
[0087] The present invention also relates to a solventless process for producing a Li-ion battery electrode, said process comprising: - mixing the active fillers, the polymeric binder, the conductive fillers and any additives by a process making it possible to obtain an electrode formulation that can be applied to a metal support by a solvent-free process, - depositing said electrode formulation on a metal substrate by a "solvent-free" process to obtain a Li-ion battery electrode; and - Consolidating the electrodes by heat treatment (application of temperatures in the range of up to 50° C. above the melting temperature of the polymer without mechanical pressure) and / or thermomechanical treatment, such as calendering or thermocompression.
[0088] A "solvent-free" process is understood to mean a method which does not require a step of evaporation of residual solvent downstream of the deposition step.
[0089] Another embodiment of a method for manufacturing an electrode includes: - mixing the active fillers, the polymer binder and the conductive fillers by a method making it possible to obtain an electrode formulation in which the constituents are homogeneously mixed, - producing a free-standing film of the formulation by a thermomechanical process, such as extrusion, calendering or thermocompression, - depositing a free-standing film on a metal substrate by calendering or thermocompression methods; and - Consolidating the electrode by thermal and / or thermomechanical treatment, for example calendering. This final step is optional if the previous steps have already achieved a sufficient level of adhesion and / or porosity.
[0090] Solvent free mixing processes for various components of electrode formulation include, but are not exhaustive, stirring mixing, air jet mixing, high shear mixing, V-mixer mixing, screw mixer mixing, double cone mixing, drum mixing, conical mixing, double Z-arm mixing, fluidized bed mixing, planetary mixer mixing, mechanofusion mixing, extrusion mixing, calendaring mixing, milling mixing.
[0091] Other mixing methods include mixing options using a liquid such as water, for example spray drying (co-atomization), or spraying a liquid containing the binder and / or conductive filler into a fluidized powder bed of the active filler.
[0092] The metal support of the electrodes is generally made of aluminum for the cathode and copper for the anode. The metal support may be surface-treated and may have a conductive primer with a thickness of 5 μm or more. The support may also be a woven or non-woven carbon fiber fabric.
[0093] Consolidation of the electrode is achieved by heat treatment, by passage through an oven, under infrared lamps, by calendering with heated rollers, or by squeezing with heated plates. Another alternative consists of a two-stage process.
[0094] First, the electrode is subjected to a heat treatment in an oven, under an infrared lamp, or by contacting it with a heated plate without pressure. Then, a compression step at ambient or elevated temperature is performed by calendering or plate squeezing. This step can adjust the porosity of the electrode and improve its adhesion to the metal substrate.
[0095] The present invention also relates to a Li-ion battery electrode produced by the above method.
[0096] According to one embodiment, the electrode is an anode.
[0097] According to one embodiment, the electrode is a cathode.
[0098] The present invention also provides a Li-ion secondary battery comprising a negative electrode, a positive electrode, and a separator, at least one of the electrodes being as described above.
[0099] The present invention also provides a supercapacitor comprising at least one such electrode. EXAMPLES
[0100] The following examples illustrate, but do not limit, the scope of the invention.
[0101] Sample 1 - Preparation of PTFE latex Water, initiator, chain transfer agent, non-fluorinated emulsifier and tetrafluoroethylene are introduced into the reactor. The polymerization is carried out at a temperature of 68° C. and at a pressure of 3000 kPa. After 180 minutes, a latex with a solids content of 29% is obtained. The primary particle size is 250 nm (D50).
[0102] Sample 2 - Preparation of PTFE powder The latex of Sample 1 is then spray dried to obtain PTFE powder.
[0103] Sample 3 - Preparation of PVDF latex Water, initiator, chain transfer agent, non-fluorinated emulsifier and vinylidene fluoride are introduced into the reactor. The polymerization is carried out at a temperature of 85° C. and a pressure of 9000 kPa. After 180 minutes, a latex with a solids content of 37% is obtained. The primary particle size is 225 nm (D50).
[0104] Sample 4 - Preparation of PVDF powder A latex corresponding to sample 3 is spray dried to obtain a PVDF powder.
[0105] Sample 5 – Preparation of PVDF and PTFE Powder Mixture 750 g of PTFE powder corresponding to sample 2 and 250 g of PVDF powder corresponding to sample 4 are introduced into a Henschel FM10 powder mixer over a period of 2 minutes. The mixture is mixed at a speed of 20 m.s at the tip of the paddle. -1 Stir for 2 minutes at a rotation speed such that
[0106] Sample 6 - Preparation of PTFE / PVDF composite binder by co-spraying 1.034 kg of PTFE latex corresponding to sample 1, 0.27 kg of PVDF latex corresponding to sample 3 and 0.696 kg of water are mixed to adjust the dry extract content to 20% of PVDF+PTFE polymer. Antifoam product (Byk 019) is also added. The addition is carried out in 5 vessels under medium stirring (10 rpm) at an ambient temperature of 20° C. The aqueous dispersion obtained is easily pumpable. The PTFE latex / PVDF latex mixture thus prepared is then pumped under medium stirring (10 rpm) and co-sprayed using the following operating conditions: Co-atomizer inlet temperature: 175℃ Co-injector outlet temperature: 55℃ Compressed air: 220kPa 400g of PVDF / PTFE composite powder can be prepared by co-spraying PVDF latex particles and PTFE latex particles. The composite powder contains 25% by weight of PVDF and 75% by weight of PTFE. The size of the formed secondary particles is 23μm (D50).
[0107] Sample 7 - Preparation of core-shell structure, PTFE core / PVDF shell Water, initiator, chain transfer agent, non-fluorinated emulsifier and tetrafluoroethylene are introduced into the reactor. The polymerization is carried out at a temperature of 68° C. and at a pressure of 3000 kPa. The total reaction volume is 2 1. After 180 min, a latex with a solids content of 29% is obtained. The latex thus obtained is then adjusted to 20% dry extract by adding water (900 g). The temperature is then increased to 90° C. and the pressure is increased to 4500 kPa by continuously adding VF2 to the reactor. The addition of potassium persulfate initiator initiates the polymerization of the PVDF shell around the PTFE core. After 60 min of polymerization, a stable latex with a particle size of 280 nm (D50) is obtained. The mass composition is 75% PTFE, 25% PVDF. The solids content obtained is 25%. The total amount of VF2 consumed is 193 g.
[0108] Sample 8 - Preparation of core-shell structure, PVDF core / PTFE shell Water, initiator, chain transfer agent, non-fluorinated emulsifier and PVDF are introduced into the reactor. The polymerization is carried out at a temperature of 90° C. and at a pressure of 4500 kPa. The total reaction volume is 2 1. After 180 minutes, a latex with a solids content of 37% is obtained, with a primary particle D50 size of 225 nm. The latex thus obtained is then adjusted to 15% dry extract by the addition of water (2933 g). The temperature is then reduced to 70° C. and the pressure is reduced to 3000 kPa by the continuous addition of TFE to the reactor. The addition of potassium persulfate initiator initiates the polymerization of the PTFE shell around the PVDF core. After 200 minutes of polymerization, a stable latex with a particle size of 338 nm (D50) is obtained. The mass composition is 75% PTFE, 25% PVDF. The solids obtained are 37.5%.
[0109] Standard electrode formulation: active material, conductive filler, e.g. carbon black (also graphene, carbon nanotubes, vapor grown carbon fibers (VGCF)), PVDF binder
[0110] Electrode manufacturing process The active material binder / conductive filler mixture is produced in two steps. First, the active fillers are mixed with the conductive fillers by a solvent-free process. In the second step, the binder is mixed with the active fillers + conductive filler premix. As a solvent-free mixing process of the various components of the formulation, a Henschel FM10 high speed paddle mixer was used with a paddle tip speed of 20 m.s. -1 The rotation speed was set to 100° C. for 2 minutes.
[0111] The composition is then prepared in the form of a free-standing film by compression using a press with heated parallel plates, which has a density of 25 mg / cm 2 This is done by depositing the formulation on a siliconized membrane so as to obtain a basis weight of 100 g / g. Then a second membrane of siliconized paper is deposited on the surface of the deposit. The assembly consisting of the first layer of siliconized paper, the formulation and the second layer of siliconized paper is then compressed at 200° C. and 700 kPa for 5 minutes. After the compression step, the assembly is removed from the press and allowed to cool to ambient temperature. After removing the siliconized paper layer, a free-standing membrane is obtained. In a second step, the free-standing membrane is pressed onto an aluminum current collector under the same conditions as for the production of the free-standing membrane.
[0112] The conditions for the preparation of the membrane and the final cathode were adjusted to obtain a thickness of 75 μm and a porosity of 32-34%, calculated indirectly according to the basis weight based on the theoretical weight per unit surface area.
[0113] Membrane operability measurements The membrane is subjected to elongation at break tests and classified to determine its operability, ranging from H0 (instantaneous break) to H3 (elongation greater than 3% at break).
[0114] Adhesion Measurement A 180° peel test was carried out in a dynamometer using test pieces cut to 15 cm in length and 25 mm in width. A double-sided adhesive is used to evaluate the peel force. One side of the adhesive is glued onto an electrode and the other side onto a rigid metal support having a thickness of a few millimeters. The rigid support is fixed to the lower jaw of the dynamometer and the end of the electrode is fixed to the upper jaw of the dynamometer. The peel force is determined by pulling at a speed of about 100-200 mm / min. This establishes the following classification: The values are only a guideline as they depend on the measuring device, the peel force, the peel speed and the adhesive supplier.
[0115] Classifications range from A0 (no adhesion) to A4 (excellent adhesion).
[0116] Measuring Flexibility - Empirical Testing (as described in U.S. Patent Application Publication No. 2002 / 0168569) Test pieces 5 cm long and at least 2 cm wide are cut from the electrodes. These test pieces are then wrapped around or bent onto a metal bar with a diameter of 1 mm. The surface is then visually inspected to identify cracks and establish the following classification:
[0117] Classifications range from F0 (very poor flexibility) to F4 (excellent flexibility).
[0118] [Table 1]
Claims
1. A fluoropolymer binder for lithium ion batteries, the binder being in the form of a powder, comprising a mixture of a polytetrafluoroethylene (PTFE) phase formed from primary particles of PTFE having a size in the range of 10 nm to 1 μm and a polyvinylidene fluoride (PVDF) phase formed from primary particles of PVDF having a size in the range of 10 nm to 1 μm.
2. 2. The binder of claim 1, wherein the PTFE particles have a size in the range of 50 nm to 500 nm.
3. The binder of claim 1, wherein the PVDF particles have a size in the range of 50 nm to 500 nm.
4. 2. The binder of claim 1, wherein the PVDF is selected from polyvinylidene fluoride homopolymers or copolymers of vinylidene fluoride with at least one comonomer selected from vinyl fluoride, tetrafluoroethylene, hexafluoropropylene, 3,3,3-trifluoropropene, 2,3,3,3-tetrafluoropropene, 1,3,3,3-tetrafluoropropene, hexafluoroisobutylene, perfluorobutylethylene, 1,1,3,3,3-pentafluoropropene, 1,2,3,3,3-pentafluoropropene, perfluoro(propyl vinyl ether), perfluoro(methyl vinyl ether), bromotrifluoroethylene, chlorofluoroethylene, chlorotrifluoroethylene, chlorotrifluoropropene, ethylene, and mixtures thereof.
5. A method for producing the binder according to any one of claims 1 to 4 by co-spraying a PVDF latex and a PTFE latex, comprising the steps of: a. mixing PVDF latex with PTFE latex; b. adding water to the PVDF latex / PTFE latex mixture to obtain a dry extract with a polymer content of 10% to 50% by weight; c) co-spraying the mixture thus obtained to obtain a composite powder formed of particles of PTFE and particles of PVDF. The method includes:
6. A method for producing the binder according to any one of claims 1 to 4 by polymerising PVDF in the presence of PTFE seeding.
7. A method for producing the binder according to any one of claims 1 to 4 by polymerising PTFE in the presence of PVDF seeding.
8. A Li-ion battery electrode comprising an active filler for the anode or cathode, a conductive filler, and the fluoropolymer binder of any one of claims 1 to 4.
9. The active filler is selected from the group consisting of lithium metal, graphite, silicon / carbon composite, silicon, graphene, fluorographite of the CFx type, where x is between 0 and 1, and LiTi for the negative electrode. 5 O 12 9. The electrode of claim 8, wherein the titanates are selected from the group consisting of titanates of the formula:
10. The active filler is LiMO for the positive electrode. 2 Type: LiMPO 4 Type: Li 2 MPO 3 F type, M is Co, Ni, Mn, Fe or a combination thereof 2 MSiO 4 type, LiMn 2 O 4 Type, S 8 or formula Li where n>1 2 9. The electrode according to claim 8, wherein the active material is selected from the group consisting of lithium polysulfide type active materials represented by Sn.
11. 9. The electrode of claim 8, wherein the conductive filler is selected from carbon black, graphite, natural or synthetic carbon fibers, carbon nanotubes, metal fibers and powders, conductive metal oxides, or mixtures thereof.
12. 9. The electrode of claim 8, having the following mass composition: - 50% to 99% active fillers, - 25% to 0.05% conductive filler, - 10% to 0.5% of a polymer binder, - 0% to 5% of at least one additive selected from plasticizers, ionic liquids, dispersants for conductive fillers, and flow agents for the formulation; and the sum of all these percentages is 100%.
13. 9. A method for producing a Li-ion battery electrode according to claim 8, comprising the steps of: - mixing said active fillers, said polymeric binder and said conductive fillers by a process making it possible to obtain an electrode formulation that can be applied to a metal support by a solvent-free process; - depositing said electrode formulation on said metal substrate by a solvent-free process to obtain a Li-ion battery electrode; and - consolidating said electrodes by thermal and / or thermomechanical treatment The method includes:
14. 10. A secondary Li-ion battery comprising an anode, a cathode and a separator, at least one of the electrodes having the composition of claim 8.
15. A supercapacitor comprising at least one electrode according to claim 8.